Cameras in the Streets: The Use and Evolution of Photography in Kansas, 1839-1950 - Williams, Brandon G. (Kansas State University, The Chapman Center for Rural Studies, 2017)
This paper is an in-depth documentation of where Kansas falls into the grand scheme of photography as the trend of hobby photography swept across the nation and the globe. This is accomplished by examining the different kinds of cameras that were used in early photography and by also examining trends in the nation as a whole, the state of Kansas, and finally, in a case study of the city of Clifton, Clay County, Kansas.
Brandon G. Williams, “Cameras in the Streets: The Use and Evolution of Photography in Kansas, 1839-1950,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/246.
Keywords: Washington County; Kansas; John C. Fremont; Junction City; Photography; Glass plate photography